2016
DOI: 10.1159/000445314
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Ultrasound Enhances Paclitaxel Efficacy in EMT6 Subcutaneous Tumors in Balb/c Mice

Abstract: Background: The objective of this study was to explore the effects of 30 kHz ultrasound on the efficacy of paclitaxel in subcutaneous breast tumors in Balb/c mice in vivo. Materials and Methods: 40 Balb/c female mice were divided into 5 groups: model control group, paclitaxel intraperitoneal (ip) group (20 mg/kg, ip, at 3 day intervals for a total of 3 doses (q3d×3)), paclitaxel intratumoral (it) group (20 mg/kg, it, q3d×3), paclitaxel intraperitoneal (20 mg/kg, ip, q3d×3) combined with low-frequency ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…20 found that US (1.1 MHz, 1.0 W/cm 2 , 10% duty cycle) combined with 5-FU could lead to the growth inhibition of hepatic carcinoma in nude mice. 20 Compared with Ren et al ., 41 Liu et al ., 42 and Hu et al ., 20 the frequency of ultrasound we used is lower (20 kHz). Theoretically, sound waves with lower frequencies have longer periods leading to longer MB oscillation time in the expansion phase and a larger expansion in the diameter of the MBs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…20 found that US (1.1 MHz, 1.0 W/cm 2 , 10% duty cycle) combined with 5-FU could lead to the growth inhibition of hepatic carcinoma in nude mice. 20 Compared with Ren et al ., 41 Liu et al ., 42 and Hu et al ., 20 the frequency of ultrasound we used is lower (20 kHz). Theoretically, sound waves with lower frequencies have longer periods leading to longer MB oscillation time in the expansion phase and a larger expansion in the diameter of the MBs.…”
Section: Discussionmentioning
confidence: 92%
“…US and chemotherapy increased the local concentrations of paclitaxel in the tumors and restrained tumor volume in transplanted subcutaneous EMT6 carcinomas. 42 Hu et al . 20 found that US (1.1 MHz, 1.0 W/cm 2 , 10% duty cycle) combined with 5-FU could lead to the growth inhibition of hepatic carcinoma in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…To induce subcutaneous tumors, the mice (10 per group) were each injected with 5×10 7 PC9 cells in 0.2 ml into their limbs, these mice were then divided into three groups of six mice each, and paclitaxel was administered intraperitoneally at doses of 10, 15, and 20 mg/kg every ve days, which was a reasonable dosing schedule based on relevant published studies, and its safety was con rmed by reported toxicity tests at all dose levels (13)(14)(15)(16)). The tumors were measured every three days using calipers once they were palpable, and the tumor volume was calculated as (width 2 × length)/2.…”
Section: Animal Experimentsmentioning
confidence: 99%